2011
DOI: 10.1002/pon.2050
|View full text |Cite
|
Sign up to set email alerts
|

Partners and close family members of long‐term cancer survivors: health status, psychosocial well‐being and unmet supportive care needs

Abstract: Background: A cancer diagnosis can have a profound impact on partners and close family members of patients. Little is currently known about the long-term impact.Objectives: The objective of this study is to describe health status, levels of anxiety and depression, unmet supportive care needs and positive outcomes in the partners/family members of breast, prostate and colorectal cancer survivors 5-16 years post-diagnosis.Methods: Patients in a linked study were asked to invite a partner or other close family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 36 publications
4
57
1
5
Order By: Relevance
“…They indicated that they have already received a lot of information in the hospital, or they feared that the information would be too general. Other researchers reported a similarly wide range of information needs of partners of cancer patients [7,29,30]. The different preferences regarding information needs should be considered in a Web-based intervention for partners.…”
Section: Discussionmentioning
confidence: 97%
“…They indicated that they have already received a lot of information in the hospital, or they feared that the information would be too general. Other researchers reported a similarly wide range of information needs of partners of cancer patients [7,29,30]. The different preferences regarding information needs should be considered in a Web-based intervention for partners.…”
Section: Discussionmentioning
confidence: 97%
“…Under the NHI provisions and available free access to healthcare for low-income families in Taiwan, treatment refusals remain observable among numerous lung cancer patients. Presumably, health care access is impeded by other factors for low-income families, and other factors may affect treatment decisions, example for close family members support or cancer knowledge [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…A cancer diagnosis has a strong emotional impact on the family. Reactions of fear, anxiety, sadness, and existential concerns are common and can be greater for family members than for the patient [13, 14]. Family members may perceive they are at greater risk of developing cancer due to real or perceived shared genetic or environmental risk factors and have heightened awareness about cancer and its prevention [15, 16].…”
Section: Introductionmentioning
confidence: 99%